About Synergistic Effect of Lubricant and Chemical Additives on Obtaining Quality Surface of Concrete Products - P. I. Yukhnevskiy; N. P. Dimitriadi (Наука и техника)
The paper substantiates scientific background for development of lubricant compositions used in moulds for concrete products with high-quality surface. It has been shown that consideration of interaction between air bubbles, lubricant and liquid phase of modified concrete is of great importance. A release agent must allow air to migrate to a certain extent and leave “formwork – concrete mix” interface. In this regard the lubricant must have low viscosity. In addition, the lubricant should give maximum hydrophobization to a mould and have minimal adhesion in respect of the concrete mix. Additives of hydrophobic substances in liquid lubricants significantly reduce surface porosity of products. Chemical plasticizing additives and, in particular, additives of polycarboxylate type substantially reduce surface tension of liquid sгж, thereby they significantly reduce work for fixing an air bubble on concrete surface and contribute to its ejection. In addition, adsorbed molecules of the chemical additives interfere with interaction of cement paste particles and mould surface. Polycarboxylate additive molecules diffuse from a diffuse layer of the concrete mix, fill capillaries in the lubricant film, reduce its viscosity, act as additives that regulate spreading of lubricant and facilitate removal of air bubbles in a surface layer. Experimental studies of the combined effect while using low viscosity grease based on vegetable oils and modifying additives have confirmed the above provisions. The polycarboxylate-based additive has made the greatest impact on reduction of concrete surface porosity and content of all types of pores in the concrete has been approximately at the same level.